Pengaruh Model Pembelajaran Snowball Throwing Terhadap Hasil Belajar Membaca pada Mata Pelajaran Bahasa Indonesia Siswa Kelas IV SD No. 198 Inpres Bontorita Kabupaten Takalar - Fitrih Amaliah; Rosmini Madeamin; Basse Syukroni Baso (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2023)
This study aims to describe the effect of the snowball throwing learning model on the results of learning to read Indonesian for grade IV SD students No.198 Inpres Bontorita Takalar Regency. The subjects used in the study were 30 students. This type of research is pre-experimental research in the form of Pre Test Post Test Design, namely an experiment which in its implementation only involves one class as the experimental class without any comparison class (control class).The success of the learning process in terms of aspects, namely: the achievement of completeness of students' classical Indonesian learning outcomes, student activities in learning Indonesian. Learning is said to be successful if the above aspects are fulfilled. The data collection technique used is the score data for reading results which are collected using a reading test.The results of the descriptive statistical analysis using the Snowball Throwing Learning Model for positive reading skills, students' reading skills using the Snowball Throwing learning model show better learning outcomes than before the Snowball Throwing learning model was applied. The results of inferential statistical analysis using the t test formula, it is known that the calculated t value obtained is 11.5444 with a frequency of db = 30–1 = 29, at a significance level of 5% obtained t table = 2.04523. So, t count > t table or the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted. This proves that there is influence in applying the Snowball Throwing learning model to reading skills in Indonesian language class IV SD No.198 Inpres Bontorita.